Answer:
y + 1 = 4(x - 2)
y = 4x + 11
8x - 2y = 6
Step-by-step explanation:
Following equations are parallel to the graph 4x - y = 6, because their slopes are equal (4).
y + 1 = 4(x - 2)
y = 4x + 11
8x - 2y = 6
The answer would be <span><span>f<span>−1</span></span><span>(x)</span></span>=<span>√<span>36+x</span></span>,<span>−<span>√<span>36+<span>x. I didn't know it in word form :(</span></span></span></span>
the answer would be -1,224 because the parentheses is your multiplication and the it is a negative
1: answer: 4^6 ( reduce the fraction with 4^3)
2: answer: 1 ( any nonzero expression raised to the power of 0 equals 1 )
3: answer 3^8
steps: (3^2)^4 = 3^2×4 ( to raise a power to another Power multiply the exponents)
3^2×4 = 3^8 ( multiply the 2 and the 4 exponent to get a 8 as a exponent )